1993
DOI: 10.1136/thx.48.5.506
|View full text |Cite
|
Sign up to set email alerts
|

Lung deposition patterns of directly labelled salbutamol in normal subjects and in patients with reversible airflow obstruction.

Abstract: Deposition was assessed by a dual headed gamma camera after inhalation of the drug. Results-The total mean (SD) percentage deposition of the drug in the normal subjects was 21-6% (8.9%) with the MDI alone, 20-9% (7-8%) with the AMDI with spacer, and 12-4% (3-5%) with the DPI. For the patients, the mean percentage deposition was 18-2% (7.8%) with the MDI alone, 19-0% (8-9%) with the MADI and spacer, and 11-4% (5-0%) with the DPI. Bronchodilatation achieved by the patients was similar with all three techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0
5

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(85 citation statements)
references
References 6 publications
4
75
0
5
Order By: Relevance
“…Scintigraphic and pharmacokinetic deposition studies have indicated that this device is capable of delivering a mean of 20-30% of the nominal dose to the lungs of adults [1,2]. Although it is difficult to compare results from studies utilizing different methods [3], these results suggest that the device delivers a greater proportion of the nominal dose to the lungs of adult patients than do other DPIs [4,5], metereddose inhalers (MDIs) [4,6,7], and jet nebulizers [8,9], and these results are similar to optimal values obtained using certain MDI-spacer combinations [6].In vitro deposition studies have indicated that the performance of the Turbuhaler®, and other DPIs, can be significantly influenced by the peak inspiratory flow (PIF) achieved through the device [2,5,[10][11][12][13][14][15][16]. The fine particle dose delivered by a Turbuhaler®, measured in vitro using multistage liquid impingers, decreases with decreasing flow [16].…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Scintigraphic and pharmacokinetic deposition studies have indicated that this device is capable of delivering a mean of 20-30% of the nominal dose to the lungs of adults [1,2]. Although it is difficult to compare results from studies utilizing different methods [3], these results suggest that the device delivers a greater proportion of the nominal dose to the lungs of adult patients than do other DPIs [4,5], metereddose inhalers (MDIs) [4,6,7], and jet nebulizers [8,9], and these results are similar to optimal values obtained using certain MDI-spacer combinations [6].In vitro deposition studies have indicated that the performance of the Turbuhaler®, and other DPIs, can be significantly influenced by the peak inspiratory flow (PIF) achieved through the device [2,5,[10][11][12][13][14][15][16]. The fine particle dose delivered by a Turbuhaler®, measured in vitro using multistage liquid impingers, decreases with decreasing flow [16].…”
mentioning
confidence: 65%
“…Scintigraphic and pharmacokinetic deposition studies have indicated that this device is capable of delivering a mean of 20-30% of the nominal dose to the lungs of adults [1,2]. Although it is difficult to compare results from studies utilizing different methods [3], these results suggest that the device delivers a greater proportion of the nominal dose to the lungs of adult patients than do other DPIs [4,5], metereddose inhalers (MDIs) [4,6,7], and jet nebulizers [8,9], and these results are similar to optimal values obtained using certain MDI-spacer combinations [6].…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…No difference was observed in total lung deposition when a group of patients and healthy volunteers were compared using salbutamol pMDI, although the deposition patterns were more central in the patients [20]. A breath-actuated pMDI, which triggers the inhaler at a specific inhalation flow, and thus avoids the need to co-ordinate inhalation and actuation, has been tested in patients considered to be "good" and "bad "co-ordinators [63].…”
Section: Pressurized Metered-dose Inhalermentioning
confidence: 99%
“…regional deposition data; the most usual divisions of the lungs are into central, intermediate and peripheral zones, representing mainly large, medium and small airways, respectively [19], or into a central one-third and a peripheral two-thirds of the lung fields [20]. The lung edges are usually defined either by ventilation scans using a radioactive inert gas [21], or by a transmission scan using a large flood field source [18].…”
Section: Systematic Bioavailabilitymentioning
confidence: 99%